2022
DOI: 10.1002/hep4.1918
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐analyte cell‐free DNA–based blood test for early detection of hepatocellular carcinoma

Abstract: The limited performance of guideline-recommended abdominal ultrasound and serum alpha-fetoprotein (AFP) highlights the urgent, unmet need for new biomarkers for more accurate detection of early hepatocellular carcinoma (HCC). To this end, we have conducted a prospective clinical validation study to evaluate the performance of the HelioLiver Test, a multi-analyte blood test combining cell-free DNA methylation patterns, clinical variables, and protein tumor markers. A blinded, multicenter validation study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…Early‐stage HCC sensitivity of the cfDNA panel was significantly higher than AFP and the GALAD panel (82% vs. 40% and 71%, respectively), although AFP and GALAD both had higher specificities 6 . A subsequent multi‐center case–control study similarly evaluated a methylated DNA panel and found superior sensitivity for early‐stage HCC compared to AFP and GALAD (76% vs. 57% and 65%, respectively) albeit with lower specificities (91% vs. 97% and 94%, respectively) 7 . Based on these promising data, both panels are currently undergoing prospective validation.…”
Section: Liquid Biopsy For Early Detection Of Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Early‐stage HCC sensitivity of the cfDNA panel was significantly higher than AFP and the GALAD panel (82% vs. 40% and 71%, respectively), although AFP and GALAD both had higher specificities 6 . A subsequent multi‐center case–control study similarly evaluated a methylated DNA panel and found superior sensitivity for early‐stage HCC compared to AFP and GALAD (76% vs. 57% and 65%, respectively) albeit with lower specificities (91% vs. 97% and 94%, respectively) 7 . Based on these promising data, both panels are currently undergoing prospective validation.…”
Section: Liquid Biopsy For Early Detection Of Hccmentioning
confidence: 99%
“…6 A subsequent multi-center case-control study similarly evaluated a methylated DNA panel and found superior sensitivity for early-stage HCC compared to AFP and GALAD (76% vs. 57% and 65%, respectively) albeit with lower specificities (91% vs. 97% and 94%, respectively). 7 Based on these promising data, both panels are currently undergoing prospective validation.…”
Section: Liquid Biopsy For E Arly Detection Of Hccmentioning
confidence: 99%
“…The Helio ECLIPSE™ platform was used to analyze cfDNA extracted from patient specimens as previously described 40 . Brie y, total cfDNA was isolated from specimens by using either (Cohort 1) a QIAsymphony DSP Circulating DNA Kit (QIAGEN, USA) or (Cohort 2) the EliteHealth cfDNA Extraction Kit (EliteHealth, China).…”
Section: Targeted Em-seq Of Cfdnamentioning
confidence: 99%
“…Moss et al 51 described a sensitivity of 80% and specificity of 97% (n = 235) when using cfDNA to diagnose treatment-naïve breast cancer on the basis of a breast-specific DNA methylation signature. In a clinical validation study on hepatocellular carcinoma (HCC), Lin et al 52 evaluated a comprehensive analysis method integrating cell-free DNA methylation patterns, clinical variables and protein tumour markers. This multianalyte test (AUC of 0.944) showed better diagnostic performance than both alpha foetal protein (AFP, a biomarker of HCC; AUC of 0.851) and the GALAD score (an evaluation system including sex, age and AFP to detect HCC; AUC of 0.899).…”
Section: Cell-free Nucleic Acids (Cfdna and Cfrna)mentioning
confidence: 99%
“…described a sensitivity of 80% and specificity of 97% ( n = 235) when using cfDNA to diagnose treatment‐naïve breast cancer on the basis of a breast‐specific DNA methylation signature. In a clinical validation study on hepatocellular carcinoma (HCC), Lin et al 52 . evaluated a comprehensive analysis method integrating cell‐free DNA methylation patterns, clinical variables and protein tumour markers.…”
Section: Cell‐free Nucleic Acids (Cfdna and Cfrna)mentioning
confidence: 99%